Analysis of Electric Power Usage Level and Total Electricity Consumption Duration at Binjai City - Wardiman Anugerah Harefa; Solly Aryza; Muhammad Erpandi Dalimunthe (INFOKUM, 2025)
Electricity is a fundamental source of energy that supports daily human activities across residential, commercial, and industrial sectors. As urban development and population growth continue in cities like Binjai, the demand for electricity is steadily increasing. Efficient management of electrical energy usage is crucial to ensure sustainability, reduce environmental impact, and maintain cost-effective energy supply systems. This study aims to analyze the level of electric power usage and the total duration of electricity consumption across various consumer categories in Binjai City. A descriptive quantitative approach is applied by collecting data from utility consumption records, calculating average power usage (kW), total energy consumed (kWh), and determining usage intensity based on national standards. The results indicate that household consumption accounts for the highest usage time, while industrial consumers exhibit the highest average power demand. Several households fall into the high Energy Consumption Intensity (ECI) category, suggesting potential energy inefficiencies. The study emphasizes the importance of awareness, consumption monitoring, and load management strategies to promote energy savings. The findings of this research can be used by local authorities and energy providers to improve electricity distribution planning, encourage responsible usage behavior, and support the development of sustainable urban energy systems.